The role of posturography on the initial stage of sports training - Podlivaev, B.; Kurashvili, V.; Sinyuchkova, E.; Kuznetsov, A. (BIO Web of Conferences, 2020)
One of the main directions in the wrestlers training on the initial stage of sports training is the formation of the wrestler`s motion coordination abilities. Equilibrium function and anthropometric data including wrestler`s gender have essential differences in connection both with the child`s biological specialities and choosen athletic discipline special aspects. This research is focused on comparsion of variations in kinetic postural control affected by the lassitude among young athletes and non-athletes. 16 girl childs - freestyle wrestlers participates in this research. They are on initial stage of sports training. The control group consisted of 14 girl childs irrelevant to sports. There was made a hypothesis that the wrestlers lassitude can be measured subjectively (with the Borg scale) and objectively (with the stabilometrics), and that the wrestlers will better control their body position than the girls irrelevant to sports. Tecnobody Pro-Kin stabilometric platform was used to measure postural balance. There was determined statistically significant positive relationship of the investigated parameters changes between groups. As a result of the research we can make a conclusion that the offered method can provide reliable data concerning wrestler`s lassitude level. Analogues data are received with the rating of perceived exertion by Borg`s scale. As the result we can conclude that the offered postural balance research method is valid for the wrestler`s lassitude rating and can be used as a component of the complex athletes control system.